Aspek Hukum dan Etika dalam Pertanggungjawaban Notaris terhadap Akta yang Batal - Hafiz, Muhammad; Sahnan, Sahnan; Mubarak, Alfian (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study examines the legal and ethical aspects of a notary's accountability for deeds that are null and void by law. As a public official, a notary plays a strategic role in drafting authentic deeds that serve as written evidence in various legal transactions. However, deeds prepared by notaries can be declared null and void if they violate legal provisions or formal procedures. This study explores the notary's responsibilities under the Notary Office Act (UUJN) and the relevant principles of professional ethics. The primary focus of the research is to identify the forms of a notary's accountability, including civil, criminal, and administrative responsibilities, as well as how professional ethics can serve as guidelines to prevent violations. Using a normative-juridical approach, this study reveals that a notary's accountability is not only oriented toward legal aspects but also toward integrity and public trust, which are the foundation of the notary profession. The study provides recommendations to strengthen mechanisms for supervising and guiding notaries to minimize the risk of violations in performing their duties.